2014
DOI: 10.1111/tri.12410
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation from donors outside standard acceptability criteria - are they really marginal?

Abstract: SummaryLung transplantation (LTx) from "extended donor criteria" donors may reduce significantly organ shortage. However, its influence on results remains unclear. In this study, we evaluate retrospectively the results of LTx from donors outside standard criteria: PaO2/FiO2 ratio < 300 mmHg, age over 55 years, and history of smoking > 20 pack-years. Two hundred and forty-eight patients underwent first time LTx in our institution between January 2007 and January 2013. Seventy-nine patients (Group I) received or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…However, results from these marginal donor lungs for conventional transplantation have been mixed. A number of studies have reported good short‐ and medium‐term results using non‐optimal lung donors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results from these marginal donor lungs for conventional transplantation have been mixed. A number of studies have reported good short‐ and medium‐term results using non‐optimal lung donors …”
Section: Discussionmentioning
confidence: 99%
“…The shortage of lung donors is one of the main obstacles when aiming for a perfect match . The use of marginal donors is one of the strategies for increasing the lung graft pool . However, the average wait time is still too long, resulting in a considerable number of deaths on the waiting list .…”
Section: Introductionmentioning
confidence: 99%
“…The age of donors may be important for scaffold production and donor cell isolation. Studies have indicated that lungs from donors > 55 years may be used for transplant, with an acceptable outcome (Zych et al, ). Our lung donors were all aged < 55 years but further work needs to be done to examine the influence of human donor age on AC scaffold production, as well as cell and bioengineered tissue viability.…”
Section: Discussionmentioning
confidence: 99%
“…5 Above that, lungs from donors with conditions like lung contusion 6 or pulmonary embolism 7 have been successfully transplanted. 3,[8][9][10] The worldwide increase of transplantation of these extended criteria donor (ECD) lungs has had an important effect on transplant numbers, and a further increase seems possible with the widespread clinical application of ex vivo lung perfusion techniques for evaluation and/or reconditioning of ECD lungs. [11][12][13] With respect to donor age, a maximum of 55 years was set in 1999 by Novick et al 14 Although this age has been gradually increased in the meantime, still the largest remaining underutilized donor segment is the elderly.…”
Section: J Heart Lung Transplant ]]]];]:]]]-]]]mentioning
confidence: 99%